2014
DOI: 10.1080/01490400.2014.938846
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Event Service Quality and Satisfaction on Happiness Among Runners of a Recurring Sport Event

Abstract: The consumption of sport events through direct participation can influence participants' perception of happiness with that experiential purchase given the time and resources invested in that experience. The purpose of the study was to examine how sport event service quality aspects operationalized through the physical environment, interaction, and outcome factors influence overall satisfaction with the event and experiential happiness. Data were collected from 300 runners who participated in 5k and 10k races. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
114
1
48

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(179 citation statements)
references
References 90 publications
16
114
1
48
Order By: Relevance
“…The other possible reason could be that interaction between sports tourists and the staff was limited. This is consistent with some previous findings (Theodorakis et al, 2015;Theodorakis, Tsigilis, & Alexandris, 2009) that interaction quality did not affect skiers' psychological attachment or loyalty to the ski center, unlike the physical environment and outcome quality. Also, Theodorakis et al (2015) found an interaction component examined in the study had no significant effect on event satisfaction because runners in 5 km and 10 km races had little time to interact with event personnel.…”
Section: Structural Equation Modeling Analysissupporting
confidence: 82%
See 3 more Smart Citations
“…The other possible reason could be that interaction between sports tourists and the staff was limited. This is consistent with some previous findings (Theodorakis et al, 2015;Theodorakis, Tsigilis, & Alexandris, 2009) that interaction quality did not affect skiers' psychological attachment or loyalty to the ski center, unlike the physical environment and outcome quality. Also, Theodorakis et al (2015) found an interaction component examined in the study had no significant effect on event satisfaction because runners in 5 km and 10 km races had little time to interact with event personnel.…”
Section: Structural Equation Modeling Analysissupporting
confidence: 82%
“…However, some have argued the SERVQUAL model is not fully applicable to sport, leisure, and recreational settings (Kouthouris & Alexandris, 2005). An alternative model, proposed by Brady and Cronin Jr (2001) and Rust and Oliver (1993), has been extensively applied to outdoor leisure research (Alexandris et al, 2004;Theodorakis, Kaplanidou, & Karabaxoglou, 2015). Theodorakis et al (2015) posit three-dimension assessment of outdoor leisure services: outcome quality, interaction quality, and physical environment quality.…”
Section: Service Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…According to Sato, Jordan, and Funk (2014); event participation is an active leisure that increases the quality of life. Thus quality of the experience as a product is the most important part of sport events that consumers need to be considered (Theodorakis, Kaplanidou, & Karabaxoglou, 2015).…”
Section: Introductionmentioning
confidence: 99%